Customer Satisfaction sebagai Intervening Variabel dalam Mempertahankan Customer Behavior Intention Pasien di Rumah Sakit PHC Surabaya - Nur Jannah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the effect of customer experience on customer satisfaction in Covid-19 patients at PHC Surabaya Hospital, the effect of customer satisfaction on customer behavioral intention in Covid-19 patients at PHC Surabaya Hospital, the effect of customer experience on customer behavioral intention. through customer satisfaction for Covid-19 patients at PHC Surabaya Hospital. The method applied in this research is explanatory research with a quantitative approach. The population in this study used all Covid-19 patients who had visited the PHC Surabaya Hospital. The data sample in this study has been determined using a quota sample of 100 people. This study took 2 (two) types of data collection techniques, namely questionnaires and documentation. After the data has been collected, data analysis is carried out using SEM analysis techniques with the help of the SmartPLS program. The results showed that customer experience had a significant effect on customer behavioral intention in Covid-19 patients at PHC Surabaya Hospital. Customer experience has a significant effect on customer satisfaction for Covid-19 patients at PHC Surabaya Hospital. Customer satisfaction has a significant effect on customer behavioral intention in Covid-19 patients at PHC Surabaya Hospital. Customer experience has a significant effect on customer behavioral intention through customer satisfaction for Covid-19 patients at PHC Surabaya Hospital.